L'intérieur dell'usad'ba-museo nobiliare: significati artistici e culturali - Olga Bogdanova (eSamizdat)
The author focuses on the ‘usad’ba text’ of Russian literature of the 1920s. The article explores the role of the artistic details associated with the image/representation of interiors, paintings, furniture, textiles and accessories of estate-museums located in former landowners’ estates on the territory of Soviet Russia that survived the revolutionary storms and civil war in the first decade of the new government. It aims to show how the authors’ reproductions, selections and combinations of these details not only characterize the points of view of the narrators and other characters from different social strata, which show the intermedial range of each exhibition, but also combine them to create specific value meanings, characterizing the different periods of Russian cultural history.